Taxonomic validity and phylogenetic relationships of a newly-described tooth-carp, Aphanius mesopotamicus Coad, 2009 (Teleostei: Cyprinodontidae) - Alavi-Yeganeh, Mohammad Sadegh; Keivany, Yazdan; Seyfabadi, Jafar; Kazemi, Bahram; Wallis, Graham P. (Zootaxa, 2014)
Variation among complete cytb sequences (1140 bp) of Aphanius mesopotamicus Coad, 2009 was compared with closely related species, to investigate the validity of this taxon as a newly-described tooth-carp based on morphological characteristics. Maximum likelihood and Bayesian likelihood trees supported the monophyly of A. mesopotamicus and its sister group relationship to A. sophiae. Some 10–16 differences were found when compared to four different population samples of A. sophiae, whereas, intraspecific differences were only up to 6 bp. These distances suggest divergence from a common ancestor with A. sophiae at roughly 1 million years ago. These results are congruent with morphology-based hypotheses, indicating a recent speciation event.